Protocol for the ONLOOP trial: pragmatic randomized trial evaluating a province-wide system of personalized reminders for evidence-based surveillance tests in adult survivors of childhood cancer in Ontario - Shuldiner, Jennifer; Lam, Emily; Shah, Nida; Grimshaw, Jeremy; Desveaux, Laura; Heisey, Ruth; Taccone, Michael S.; Taljaard, Monica; Thavorn, Kednapa; Hodgson, David; Gupta, Sumit; Lofters, Aisha; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Childhood cancer treatment while often curative, leads to elevated risks of morbidity and mortality. Survivors require lifelong periodic surveillance for late effects of treatment, yet adherence to guideline-recommended tests is suboptimal. We created ONLOOP to provide adult survivors of childhood cancer with detailed health information, including summaries of their childhood cancer treatment and recommended surveillance tests for early detection of cardiomyopathy, breast cancer, and/or colorectal cancer, with personalized reminders over time. Methods This is an individually randomized, registry-based pragmatic trial with an embedded process and economic evaluation to understand ONLOOP’s impact and whether it can be readily implemented at scale. All adult survivors of childhood cancer in Ontario overdue for guideline-recommended tests will be randomly assigned to one of two arms: (1) intervention or (2) delayed intervention. A letter of information and invitation will detail the ONLOOP program. Those who sign up will receive a personalized toolkit and a screening reminder 6 months later. With the participants’ consent, ONLOOP will also send their primary care clinician a letter detailing the recommended tests and a reminder 6 months later. The primary outcome will be the proportion of survivors who complete one or more of the guideline-recommended cardiac, breast, or colon surveillance tests during the 12 months after randomization. Data will be obtained from administrative databases. The intent-to-treat principle will be followed. Based on our analyses of administrative data, we anticipate allocating at least 862 individuals to each trial arm, providing 90% power to detect an absolute increase of 6% in targeted surveillance tests completed. We will interview childhood cancer survivors and family physicians in an embedded process evaluation to examine why and how ONLOOP achieved success or failed. A cost-effectiveness evaluation will be performed. Discussion The results of this study will determine if ONLOOP is effective at helping adult survivors of childhood cancer complete their recommended surveillance tests. This study will also inform ongoing provincial programs for this high-risk population. Trial registration ClinicalTrials.gov NCT05832138.